Will the Policy Instruments Mix Promote the Facility Input of Care Institutions for Older People in China? - Fen Zhang; Fen Zhang; Xiaodong Di; Xiao Yang; Xiaotian Yang; Quanbao Jiang; Changhong Yuan (Frontiers Media S.A., 2022)
Promoting the facility input of care institutions for older people is the key to the development of the care for older people. With a steady increase in the proportion of older people in China, institutional care services are considered as an important tool for older people. Policies such as government bed subsidies and tax incentives are accelerating the development of institutional care services. However, when the care for older people related policy instrument mixes lacks overall comprehensiveness, consistency and balance, the policy instrument mixes may become a "policy mess", in turn, affecting the development of care institutions for older people. Studies focusing on the combined effects of different characteristics of a policy instrument mix are scarce. To understand how to better use the policy mix to facilitate the care for older people, it is necessary to analyze the characteristics of care policies for older people and its role in the construction of care institutions for older people. Therefore, this study analyzes the impacts of comprehensiveness, consistency, and balance of policy instruments on the facility input of care institutions for older people. An empirical analysis of related policies from 2011 to 2019 in China shows that a synergetic effect exists between the policy instrument mix and the facility input of care institutions for older people. This study points that the comprehensiveness and consistency of the policy instrument mix positively affect the facility input of care institutions for older people, while the impact of balance is not significant. It not only provides feasible policy suggestions for China's policy-making departments to optimize the care for older people related policies, but also helps care institutions for older people further understand the characteristics of policy portfolios and realize sustainable development.